GROSS ANATOMICAL AND MORPHOMETRICAL STUDY ON SCAPULA OF THE LEOPARD (Panthera pardus anthera pardus) - DEVENDRA PODHADE; R. VAISH,; ,YOGITA PANDAY; RANJEET HARNE (The Bioscan, 2019)
Leopard is listed in Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Poaching of wild animals, particularly of leopard for bone trade has been increased and prescribed as substitutes for Tiger body parts to use to prepare Chinese Traditional Medicine (CTM). Literature regarding the gross morphological and morphometrical features are scanty. Hence, gross morphological and morphometric study conducted on scapulae of 4 adult leopards. The information gathered by the study will be of academic importance. Scapular spine divided the surface into two equal fossa. The costal surface was wide and the cranial part of the surface was deeply concave, whereas caudal part was flattened. The mean length and height of scapular spine were 15.32 ± 0.95 cm and 2.4 ± 0.10 cm, respectively. Distance between glenoid cavity and acromion process was 1.32 ± 0.7 cm.